The relationship between work environment and employees job satisfaction of non-academic staff at Universiti Teknologi Mara Cawangan Kelantan Kampus Machang (UiTM) / Maria Muhammad Nasir - Muhammad Nasir, Maria (2020)
This purpose of this study is to find the relationship between work environment and employees’ job satisfaction at Universiti Teknologi Mara Cawangan Kelantan Kampus Machang (UiTM). Literature review has already discussed in detail about job satisfaction, relationship with co-workers, job security and work-life balance. The data and information were collected using questionnaire. The population were 251 employees from eight (8) departments of Non-Academic Staff at Universiti Teknologi Mara Cawangan Kelantan Kampus Machang (UiTM). The sample size was 152 were identified using stratified random sampling technique. Only 124 questionnaires were returned and valid for further action. The data were analysed using Statically Package for Social Science (SPSS) Version 23. The result from finding identified a correlation exist between work environment and employees’ job satisfaction of Non-Academic Staff at Universiti Teknologi Mara Cawangan Kelantan Kampus Machang (UiTM). The result found out that the variables between relationship with co-workers and job satisfaction were strong and positive relationship. Aside from that, there were positive relationship between work environment (job security (r=0.770), relationship with co-worker (r=0.773) and work-life balance (r=0.701)) and employees’ job satisfaction. For future research, it is advisable to study this topic on deeper levels with lots of variables and also include academic staff also. For future research it should be included all staff from UiTM Kelantan